Sintesis Biodiesel dari Minyak Jelantah Menggunakan Katalis Bentonit, K-Bentonit Dan K-Bentonit Terimpregnasi CaO - Hasmalina Nasution; Wahyuni Puspita Sanda; Rahmadini Syafri; Sri Hilma Siregar; Yuhelson; Prasetya (Sistem Informasi, 2021)
Biodiesel is an alternative fuel for diesel engines produced by a transesterification reaction between vegetable oils or animal fats containing triglycerides and alcohol, one of which is methanol. The use of homogeneous base catalysts in the synthesis of biodiesel still poses a problem for the environment because it is difficult to separate, therefore, researchers use variations of heterogeneous base catalysts. The synthesis of biodiesel from used cooking oil was carried out through a transesterification reaction with technical methanol with a catalyst of CaO impregnated Bentonite, K-Bentonite and Bentonite using the reflux method at 65ºC for 2 hours. The ratio of the volume of oil, methanol, and catalyst used is 5:1:1%-w oil. Based on the research that has been done, the yield of each catalyst is 84.85% bentonite, 84.24% K-bentonite and 89.27% ​​K-bentonite-CaO. The characteristics of biodiesel obtained from each of these catalysts such as calorific value and density have met the quality requirements of the Indonesian National Standard (SNI 7182-2012), except for the acid number and kinematic viscosity which still exceed the quality requirements of SNI 7182-2012.